Optimizing The Role of The Riau Regional Police Mobile Brigade Unit in Countering Radicalism Based on Law No. 5 of 2018 Concerning The Eradication of Criminal Acts of Terrorism - Lamhot Barus; Ahmad Ansyari Siregar; Nimrot Siahaan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Radicalism is a serious threat to national security that develops through various channels, including social media and transnational ideological networks. Riau Province, as a strategic region, has experienced radical actions that threaten security stability, thus requiring optimization of the role of law enforcement officers, particularly the Mobile Brigade Unit of the Riau Regional Police. This study aims to analyze the role of Mobile Brigade in countering radicalism based on Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. The research method used is normative juridical with a legislative approach, conceptual, and qualitative analysis. The results show that the Mobile Brigade of the Riau Regional Police plays a role in the preventive, repressive, and deradicalization support aspects, but its implementation still faces obstacles such as limited personnel, technological facilities, and cross-agency coordination. Optimization can be done through increasing personnel capacity, utilizing information technology, mapping vulnerable areas, and strengthening cooperation with the National Counterterrorism Agency (BNPT), Densus 88, and local governments. With this strategy, the Riau Regional Police Mobile Brigade is expected to be able to carry out its anti-radicalism function more effectively and measurably in accordance with the mandate of Law No. 5 of 2018.